Lister hooded rats as a novel animal model of attention-deficit/hyperactivity disorder. (December 2020) - Jogamoto, Toshihiro; Utsunomiya, Ryo; Sato, Arisa; Kihara, Nanako; Choudhury, Mohammed E.; Miyanishi, Kazuya; Kubo, Madoka; Nagai, Masahiro; Nomoto, Masahiro; Yano, Hajime; Shimizu, Yusuke I.; Fukuda, Mitsumasa; et al.
Abstract: Appropriate animal models are necessary to determine the molecular and cellular mechanisms underlying attention-deficit/hyperactivity disorder (ADHD). This study used a battery of behavioral tests to compare Lister hooded rats (LHRs), an old outbred strain frequently used for autistic epilepsy research, with Wistar rats and spontaneously hypertensive rats (SHRs), a commonly used ADHD model. The open field, elevated plus maze, light/dark box, and drop tests demonstrated that LHRs were the most hyperactive animals and displayed the most inattentive- and impulsive-like behaviors, which are characteristics of ADHD. The radial arm maze, social interaction, and Morris water maze tests showed that LHRs did not display deficits characteristic of autism or intellectual disability. Although LHRs did not show different monoamine contents, the mRNA expression levels of various genes linked to ADHD ( Cdh13, Drd5, Foxp2, Maoa, Sema6d, Slc9a9, and St3gal3 ) and tyrosine hydroxylase protein expression levels were lower in the prefrontal cortex of LHRs compared with that of Wistar rats or SHRs. c-Fos, synapsin I, and tau protein expression levels in the prelimbic region of the medial prefrontal cortex were also increased in LHRs compared with Wistar rats. Atomoxetine and guanfacine, commonly used non-stimulant treatments for ADHD, ameliorated ADHD-like behaviors in LHRs. These results suggest that LHRs can serve as a better ADHD model to develop novel pharmacological interventions. Highlights: Behaviors of Lister hooded rats (LHRs), Wistar rats, and SHRs were compared. LHRs displayed the most hyperactive, inattentive, and impulsive behavior. Various gene expressions linked to ADHD were low in the prefrontal cortex of LHRs. Medication for ADHD ameliorated the ADHD-like behavior of LHRs. LHRs may be a better ADHD model to investigate neurochemical backgrounds of ADHD.